Ionic origin of a negative capacitance in lead halide perovskites. Issue 3 (16th January 2017) - Kovalenko, Alexander; Pospisil, Jan; Zmeskal, Oldrich; Krajcovic, Jozef; Weiter, Martin
Abstract : The origin of a negative capacitance observed in perovskite solar cells at intermediate and low frequencies remains unclear. Low trap density macroscopic single crystal MAPbBr3 perovskites, prepared by means of an inverse temperature crystallization technique, with symmetric Au contacts is used to avoid the influence of defects and provide the information ongoing staunchly in the perovskite material. It is shown that the inductive behavior is dominant in the frequency range where capacitance possesses negative values. Accordingly, a model for the calculation of inductive elements and the description of their origin is presented. It is shown that, at high bias, there are two bias‐dependent inductive elements, which corresponds to two different components of vacancy‐assisted ionic diffusion in perovskite crystals, originating from Br – and MA + ions. Abstract : Currently perovskites are one of the most promising materials for the photovoltaics application. However, some of the specific properties of perovskites are yet to be explained. In this Letter, Kovalenko et al. report the ionic origin of the negative capacitance MAPbBr3 perovskites. It is shown that there are two bias‐dependent inductive elements, which correspond to two different components of vacancy‐assisted ionic diffusion in perovskite crystals, originating from Br – and MA + ions.